Investigating the effects of APSIM model configuration on model outputs across different environments - Chapagain, Ranju; Remenyi, Tomas A.; Huth, Neil; Mohammed, Caroline L.; Ojeda, Jonathan J. (Frontiers in Agronomy, 2023)
This is a provisional file, not the final typeset article 60% and 70% respectively, yet the relatively large standard deviations ranging from 7.1 to 30.6 mm and 0.6 to 7.7 kg ha -1 respectively, compared to the overall mean values of drainage (44.4 mm) and nitrogen leaching (3.2 kg ha -1 ), indicate significant actual uncertainty. We identified the need to include not only fractional variance of model uncertainty, but also magnitude of the contribution in measured units (e.g. t ha -1 , mm, kg ha -1 , USD ha -1 ) for crop model uncertainty assessments to provide more useful agronomic or policy decision-making information. The findings of this study highlight the sensitivity of agricultural models to the impacts of moisture availability, suggesting that it is important to give more attention to structural uncertainty when modelling dry/wet conditions depending on the output analysed.